Dynamics of laser produced plasma from foam targets for future nanolithography devices and X-ray sources - Yaoxing Wu (Nature Portfolio, 2021)
Abstract Foam targets are expected to be more efficient candidates than solid targets for laser produced plasma (LPP) for extreme ultraviolet (EUV) and X-ray radiation sources due to the expected plasma conditions that can be optimized regarding plasma opacities, volumetrics heating effects, and the produced ions debris characteristics. In this paper, a comparison of ion dynamics between low-density foam and solid Ni plasma was systematically investigated at CMUXE. The foam Ni target (density 0.6 g/cm3) and solid Ni target (density 8.9 g/cm3) were irradiated with 1064 nm Nd:YAG laser in vacuum. A Faraday cup (FC) was used to record the ion flux and time-of-flight (TOF) signals. A lower and wider TOF signal was observed for foam Ni plasma on the time scale. The average ion energy and peak of the TOF signal of solid Ni plasma were much higher than that of the foam Ni plasma. However, the total charge values between foam and solid Ni plasma were comparable indicating a more volumetric absorption of laser energy for foam Ni. The average ion energy and peak of the TOF signal of solid Ni showed a stronger angular and laser energy dependence than that of foam Ni. The plume shape of the solid Ni plasma appeared as an oblong ellipse at each time, while that of foam Ni plasma tended to be more circular, especially at early times. The results of mass ablation rate were consistent with the FC signals and showed a more intense plasma shielding for solid Ni.